2004
DOI: 10.4144/rpsj.51.52
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Carbon from Korean Anthracite by Hindered-Settling Separation

Abstract: This study was performed to investigate the efficiency of hindered-settling column for recovering carbon from Korean anthracite. Laboratory scale hindered-settling equipment was set and two coal samples were prepared for tests. For each samples, washability analyses were performed, and several set of tests were conducted to evaluate the effect of two important operating variables, set point and teeter water flow rate. Also, mathematical model of continuous hindered-settling separation was developed. Modeling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The fluidized bed gravity separator is preferred because of its ability to treat material in the size range 0.12-3.0 mm at lower-density cut points compared with the other available separators. Efficacy of hindered settling separation in combustible recovery from Korean anthracite was studied by Cho and Kim (2004). They concluded that with an increase in both the teeter water flow rate and the bed pressure, recovery increased without much deterioration in the product quality.…”
Section: Introductionmentioning
confidence: 98%
“…The fluidized bed gravity separator is preferred because of its ability to treat material in the size range 0.12-3.0 mm at lower-density cut points compared with the other available separators. Efficacy of hindered settling separation in combustible recovery from Korean anthracite was studied by Cho and Kim (2004). They concluded that with an increase in both the teeter water flow rate and the bed pressure, recovery increased without much deterioration in the product quality.…”
Section: Introductionmentioning
confidence: 98%